Educating Teachers as a Challenge for University - Morawska, Iwona; Latoch-Zielińska, Małgorzata’; Krajka, Jarosław (INSTED: Interdisciplinary Studies in Education & Society, 2012)
With proliferation of computers and increased connectivity in all spheres of life, the application of e-learning in teacher development seems to be an essential method of enhancing effectiveness of practical training, as it opens up new forms of communication and collaboration in the virtual and in the real. The aim of the present paper is to seek solutions to the problems of teaching practice organisation and implementation in order to achieve higher quality, raise effectiveness and increase impact of practical preparation of students for serving their didactic and upbringing duties at schools. Special focus is placed on the innovative creation of a virtual educational space within the Moodle Learning Management System, which would be used while preparing for and serving the teaching practice, as well as while documenting the whole experience after its completion.